Avances en la caracterización del pensamiento matemático de los docentes de básica primaria en la creación de problemas de aritmética y álgebra. (2024)
The present research proposes to deepen the characterization of the mathematical thinking of primary school teachers by creating arithmetic and algebra problems. To achieve this, the action research methodology is used where, following a continuous period of planning, action, observation and reflection, five training workshops are designed and implemented that include various activities: Workshop I of contextualization; Workshop II on creating arithmetic problems; Workshop III on developing problems based on the modification of existing arithmetic problems; Workshop IV on creating problems that involve identifying patterns; and Workshop V creating problems based on situations that involved the use of scales. In addition, a final interview is carried out with the participating teachers, to understand their ideas about this exercise that reaffirms their training activity.